Market prospect of makapuno nuts in the Philippines - Elauria, Marilyn M. (UP Los Baños Journal, 2011)
Producing makapuno nuts from makapuno-bearing coconut trees called kanuwig provides limited and unreliable supply that barely satisfies the requirement of makapuno processors and exporters. The University of the Philippines Los Baños (UPLB) developed as technology to produce coconut that bear 75 to 100% makapuno nuts through embryo culture. The technology was improved by the Philippines coconut authority (PCA) by shortening the process of production. With financial assistance from the Philippine Council of Agriculture, Forestry and Natural Resouces Research and Development (PCARRD), PCA established embryo culture laboratories to produce and sell makapuno plantlets.